Formulation and evaluation of buccal films of piroxicam co-crystals - Anand Ammanage; Paul Rodriques; Amolkumar Kempwade; Ravindra Hiremath (SpringerOpen, 2020)
Abstract Background The aim of the present study was to enhance the solubility of piroxicam (BCS class II drug) using co-crystallization technique and formulate the buccal films of selected co-crystals for improved therapeutic utilization of drug. Co-crystals of drug with various co-formers (molar ratio 1:1) were prepared by solvent evaporation method and were screened for their aqueous solubility and percent drug content. The formation of co-crystals was confirmed by FTIR, DSC and XRD. Piroxicam co-crystals loaded buccal films were prepared and evaluated for in vitro drug release, ex vivo drug permeation while safety of formulation was determined by histopathological study. Results The co-crystals prepared with different co-formers have proved their potential to improve the solubility of the drug. Co-crystals of piroxicam-sucralose have shown six-folds more solubility than parent drug. FTIR analysis indicated shifting in characteristics peaks of piroxicam. DSC analysis showed an extra exothermic peak and alteration in characteristic endothermic peak. The powder x-ray diffraction pattern exhibited changes in 2θ values of intense peaks. Thus, formation of co-crystal was confirmed. Physical characters of buccal films were found to be within limits. Formulation F6 showed highest mucoadhesive strength (5617 ± 636 dynes /cm2) while formulation F2 showed highest in vitro drug release after 8 h, i.e., 94.557%. The ex vivo drug permeation of F2 was found to be 84.74%. The hisopathological study revealed that there was no damage to buccal mucosal tissue and was found to be intact. Conclusion The piroxicam-suralose co-crystals based mucoadhesive films of piroxicam could be a better formulation approach with improved solubility, safety, and therapeutic efficacy as compared to conventional tablets. Graphical abstract